Measuring the Impact of Structural Changes to the Components of Monetary Sterilization on the Exchange Rate after Applying the Electronic Platform in Iraq for the Period (2021-2024) - Yousif, Akram Salih; Abdulkareem, Qasim Kamal; Salih, Vajin Saleem (Journal of Ecohumanism, 2024)
This study examines the impact of structural changes to the components of the monetary sterilization policy on the exchange rate after the implementation of the electronic platform in Iraq for the period 2021-2024. The Central Bank borrows a portion of the excess liquidity and accumulates it on its balance sheet as interest-bearing liabilities. This process may involve raising the legal reserve ratios, as well as the Central Bank’s intervention in the exchange market by purchasing foreign currency. The Central Bank absorbs the impact of this purchase on local liquidity, offering deposit facilities for banks with interest. and offering its transfers to banks in the secondary market. All these actions are called the sterilization policy. The external financial constraint represented by the electronic platform has led to the emergence of a new international policy that can be described as a near transformation or confiscation of the foreign currency sale mechanism. Under this policy, exchange rate movements are directly linked to the amount of foreign currency held by the sending banks, specifically those that are logistically accepted within the framework of the U.S. financial system. These banks operate through the Office of Foreign Assets Control (OFAC) within the U.S. Department of the Treasury. The research concludes that the monetary sterilization process, or the sterilization intervention of local liquidity, is divided into two windows. The first is internal, (i.e., the window of the Central Bank to buy dollars from the government from oil revenues in exchange for issuing the dinar). The second is external (i.e., to pay foreign currency for the credit lines granted to local banks). Between these two windows, there may be a certain time delay or a time race, both of which affect the exchange rate in the Iraqi economy.